2007
DOI: 10.1136/gut.2007.129130
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of bispectral index for classification of overt hepatic encephalopathy: a multicentre, observer blinded, validation study

Abstract: BIS is a useful measure for grading and monitoring the degree of involvement of the central nervous system in patients with chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
(34 reference statements)
1
23
0
2
Order By: Relevance
“…Foley et al (1950) first reported that the delta activity of the visual electroencephalogram (EEG) correlated well with the conscious state of patients with hepatic coma. Dahaba et al (2008) The results of the present study suggest that patients with hepatic encephalopathy are more sensitive to hypnotic drugs. A disorder between excitatory and inhibitory synaptic transmission in the parahippocampal gyrus might provide a possible explanation (Jenkins et al, 1996;Franks and Lieb, 1998;Mennerick et al, 1998;Yamakura and Harris, 2000).…”
Section: Fig 1 Probability Of Unconsciousness Versus the Bis Values supporting
confidence: 48%
See 1 more Smart Citation
“…Foley et al (1950) first reported that the delta activity of the visual electroencephalogram (EEG) correlated well with the conscious state of patients with hepatic coma. Dahaba et al (2008) The results of the present study suggest that patients with hepatic encephalopathy are more sensitive to hypnotic drugs. A disorder between excitatory and inhibitory synaptic transmission in the parahippocampal gyrus might provide a possible explanation (Jenkins et al, 1996;Franks and Lieb, 1998;Mennerick et al, 1998;Yamakura and Harris, 2000).…”
Section: Fig 1 Probability Of Unconsciousness Versus the Bis Values supporting
confidence: 48%
“…Therefore, BIS is widely used to quantify the hypnotic effects of anesthetics and can serve as a tool to monitor and titrate the pharmacodynamic effects of anesthetic drugs (Sandin et al, 2008). Dahaba et al (2008) graded encephalopathy using the West Haven criteria in a multicenter study, and demonstrated that the BIS can be used to grade the degree of hepatic encephalopathy in patients with chronic liver disease. They also found that BIS displayed a weak to moderate correlation with the serum concentration of ammonia and the Child-Pugh score.…”
Section: Introductionmentioning
confidence: 99%
“…The notion of "anesthetic depth" is usually associated with training experiences or memories during surgery, in which anesthesia does not prevent consciousness or even wakingup during general anesthesia. Although EEG is the gold standard used to determine electrical activity in comatose patients, standard EEG monitoring may not be feasible for all patients who require intensive care during pretransplant [55,56] . Studies show that monitoring by BIS, which was developed in order to assist with the clinical evaluation of the degree of hypnosis with anesthesia, is useful for monitoring cases of FHF [5557] .…”
Section: Bispectral Indexmentioning
confidence: 99%
“…A "profundidade anestésica" está associada à formação de experiências ou memórias durante uma cirurgia ou mesmo ao acordar durante uma anestesia geral. Embora o EEG seja o padrão-ouro usado para determinar atividade elétrica em pacientes comatosos, o monitoramento padrão do EEG pode não ser viável para todos os pacientes que requerem cuidados intensivos no pré-transplante (Vivien et al, 2002;Dahaba et al, 2008).…”
Section: íNdice Biespectralunclassified
“…Estudos demonstram que a monitoração por BIS, que foi desenvolvido para ajudar na avaliação clínica do grau de hipnose com anestesia, é útil para o monitoramento dos casos de IHF (Vivien et al, 2002;Dahaba et al, 2008). O monitor do BIS usa o sinal do EEG derivado de eletrodos localizados na região frontal, que fazem o monitoramento contínuo.…”
Section: íNdice Biespectralunclassified